Fulminant auricular mucormycosis in a diabetic patient - Girardi, Fabio Muradás; da Rocha, Anderson Lima; Sousa, Mireille Angelo Bernardes; Eidt, Michelle Virginia (Clinical and Biomedical Research, 2017)
Human mucormycosis is an atypical fungal infection that commonly affects the skin, but rarely the auricular region. A 32-year-old diabetic woman, agricultural worker, was admitted with swelling, redness and mild signs of epidermolysis of the left ear, associated with intense pain, facial paralysis and septic signs. The ear cellulitis evolved into necrosis of the same region on the following day. Surgical debridement was performed and antimycotic therapy was started with poor response. The patient died in 48h. Culture was confirmatory for Rhizopus sp. Keywords: Mucormycosis; fungal infections; diabetes; Rhizopus